1979
DOI: 10.4141/cjas79-019
|View full text |Cite
|
Sign up to set email alerts
|

POSTWEANING PLASMA CONCENTRATIONS OF LUTEINIZING HORMONE AND ESTROGENS IN SOWS: EFFECT OF TREATMENT WITH PREGNANT MARE’S SERUM GONADOTROPIN OR ESTRADIOL-17β PLUS PROGESTERONE

Abstract: concentrations of luteinizing hormone and estrogens in sows: Effect of featment with pregnant mare's serum gonadotropin or esradiol-l7B plus progesterone Can. J. Anim. .The plasma concentrations of luteinizing hormone (LH) and estrogens (E) were determined for I 2 sows, from a herd with a history of postweaning anestrus, from the day of weaning to 32 days after weaning (trial I). A linear increase in plasma LH and E was observed in six sows which remained in anestrus (LH, 0.32-0.47 ng/ml; E, 16.l-24.'7 pg/ml).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Such an increase could serve to trigger the preovulatory release of oestrogen, as has been shown to occur with maleinduced puberty in mice (Bronson & Desjardins, 1974). However, in the present results there was no post-weaning elevation in basal LH before that seen at ovulation, which is in agreement with results from other workers (Dyck, Palmer & Simaraks, 1979;Stevenson & Britt, 1980). The low lactational and post-weaning plasma LH levels observed in Group E sows is further reflected in a greatly attenuated ovulatory surge, as has been reported for sows after a 3-week lactation (Edwards & Foxcroft, 1983).…”
Section: Discussionsupporting
confidence: 93%
“…Such an increase could serve to trigger the preovulatory release of oestrogen, as has been shown to occur with maleinduced puberty in mice (Bronson & Desjardins, 1974). However, in the present results there was no post-weaning elevation in basal LH before that seen at ovulation, which is in agreement with results from other workers (Dyck, Palmer & Simaraks, 1979;Stevenson & Britt, 1980). The low lactational and post-weaning plasma LH levels observed in Group E sows is further reflected in a greatly attenuated ovulatory surge, as has been reported for sows after a 3-week lactation (Edwards & Foxcroft, 1983).…”
Section: Discussionsupporting
confidence: 93%
“…The majority of sows treated two days after weaning with 30 µg oestradiol benzoate/kg body weight returned to oestrus on or before Day 5, a time which compares favourably with the mean of 7-85 days recorded by Burger (1952) for Large White sows and with the results obtained in many commercial herds employing 3-week weaning (M.L.C., 1980). Although the interval of 3 days from oestradiol benzoate injection to overt oestrus in sows injected with 30 µg/kg on Day 2 is in agreement with published data (Rasbech, 1953;Dyck et al, 1979), the marked reduction in fertility and prolonged oestrous periods associated with the previous use of synthetic oestrogens (de la Cerna, 1956;Rigor et al, 1968;Schmidt et al, 1968) were not observed.…”
Section: Discussionsupporting
confidence: 80%
“…The treatment of sows with gonadotrophins and steroids at, or shortly after, weaning has been more successful. Weaning to oestrus intervals have been shortened by use of diethylstilboestrol (Rigor, Villareal & Illagan, 1968) or a combination of steroids (Schmidt, Jochle & Thume, 1968 ;Dyck, Palmer & Simarks, 1979) but conception rates and litter size were reduced. Gonadotrophin therapy (PMSG : hCG combina¬ tions) can shorten the weaning to oestrus interval with no detrimental effects on fertility (Rasbech, 1953;Whyte, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In the sows that remained anoestrus after weaning, there was a significant increase in mean LH concentration, but there was no accompanying linear increase in Ez secretion. Other studies have indicated that there is a linear increase in LH secretion (DYCK et al, 1979;ALMOND and DIAL, 1990) and that E2 secretion remains relatively low (ARMSTRONG and BRIIT, 1985) in sows remaining anoestrus after weaning as follicles fail to develop. In the present study, the overall mean and basal LH concentrations were higher in the sows that resumed cyclicity compared with those that remained anoestrous after weaning.…”
Section: Discussionmentioning
confidence: 97%